PERTUMBUHAN DAN SINTASAN LOBSTER AIR TAWAR (Cherax quadricarinatus) PADA SALINITAS YANG BERBEDA - Denny Indra Yudhistira (Scientific Timeline, 2022)
This experiment aims to find the data and information on suitable salinity for the growth and survival rate of freshwater lobster (red claw). The research was conducted in indoor station Kalikidang, Sokaraja, Banyumas, for 28 days. Twelve aquariums were used in this research, and the dimensions were 60x40x40 cm. In this experiment, a complete randomized design was used. The treatments applied were of different salinity, i.e., A: 0 ppt, B: 5 ppt, C: 10 ppt, and D: salinity of 15 ppt, with three replicates, respectively. The average size of the juvenile freshwater lobsters used in this experiment was 5±0,82 cm carapace width and 4,49±1,34 g body weight. During the rearing, the crabs were fed with commercial artificial feed and given twice a day, with a dosage of 15% of total body weight. The determined parameters were length, body weight, and survival rate during the experiment. The result showed that the treatment of 0-5 ppt salinity was significantly different in the growth of length and body weight and survival rate of freshwater lobster reared in the aquarium (P<0,05). The salinity of 0-5 ppt was the optimum salinity for the growth and survival rate of the red claw.